2020
DOI: 10.1111/jocd.13434
|View full text |Cite
|
Sign up to set email alerts
|

Temporal volume increase after reduction of masseteric hypertrophy utilizing incobotulinumtoxin type A

Abstract: Background:Treating the lower face with neuromodulators and targeting the masseter muscle can reduce masseteric hypertrophy but can also change the facial shape.A novel observation after the treatment of the masseter muscle with incobotulinumtoxin Type A was the increase in temporal volume. Aim:Objectively assess temporal volume increase following treatment of masseteric hypertrophy using incobotulinumtoxin Type A.Methods: Nine female patients with a mean age of 35.11 years ± 9.1 [Asian (11.1%) and Caucasian (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…It is of additional importance to note that treating the masseter muscle with neuromodulators will result in a compensatory volume increase of the temporalis muscle. 31 This will reduce temporal hollowing and can also be used to reshape the facial appearance. The amount of neuromodulator administered should be tailored to the muscle volume, sex, and ethnicity of the patient, which have been suggested to range between 8 and 10 IU per injection point in the Asian population, if the three-point injection technique is performed.…”
Section: Fascial Arrangement Of the Facementioning
confidence: 99%
“…It is of additional importance to note that treating the masseter muscle with neuromodulators will result in a compensatory volume increase of the temporalis muscle. 31 This will reduce temporal hollowing and can also be used to reshape the facial appearance. The amount of neuromodulator administered should be tailored to the muscle volume, sex, and ethnicity of the patient, which have been suggested to range between 8 and 10 IU per injection point in the Asian population, if the three-point injection technique is performed.…”
Section: Fascial Arrangement Of the Facementioning
confidence: 99%
“…20 MMH treatment may at times lead to temporal fossa volume increase, which may be secondary to masseter paralysis or a transient bulge in the muscle, which may be secondary to minor bleeding. 36,37…”
Section: F I G U R E 1 Injection Points For Masseter Botoxmentioning
confidence: 99%
“…Historically, soft‐tissue fillers have been used to ameliorate the signs of aging by targeting folds and creases, while recent developments have shown that not only signs of aging, but rather a combination of age‐ameliorating and face‐contouring treatments can be performed 9 . A sign of aging in the upper face is temporal hollowing, which is especially visible in thin patients 10‐12 . A plethora of age‐related changes contribute to hollowing of the temples, as bone remodeling, atrophy of the temporalis muscle, thinning of the skin, and deflation of the subcutaneous and deep temporal fat create the appearance of a skeletonized face 13‐15 .…”
Section: Introductionmentioning
confidence: 99%
“…9 A sign of aging in the upper face is temporal hollowing, which is especially visible in thin patients. [10][11][12] A plethora of age-related changes contribute to hollowing of the temples, as bone remodeling, atrophy of the temporalis muscle, thinning of the skin, and deflation of the subcutaneous and deep temporal fat create the appearance of a skeletonized face. [13][14][15] Previous studies have established a relationship between facial skeletonization, temporal hollowing, and postmenopausal sarcopenia.…”
mentioning
confidence: 99%